Jackson's machinery of justice - Jackson, R. M. 1903- (Cambridge University Press, 1989)
First published in 1940, R. M. Jackson's Machinery of Justice in England has long been established as the classic text on the subject, unparalleled in its lucidity, breadth of treatment and critical engagement with the issues involved. For this edition, J. R. Spencer has undertaken a further full-scale revision, incorporating such major topical innovations as the Police and Criminal Evidence Act of 1984 and the Prosecution of Offences Act, 1985